2011
DOI: 10.1647/2010-030.1
|View full text |Cite
|
Sign up to set email alerts
|

Proventricular Dilatation Disease in Cockatiels (Nymphicus hollandicus) After Infection With a Genotype 2 Avian Bornavirus

Abstract: An isolate of genotype 2 avian bornavirus (ABV) was recovered from a cockatiel (Nymphicus hollandicus) that was euthanatized for an unrelated lesion and showing no clinical evidence of proventricular dilatation disease (PDD). On histopathologic examination, mild inflammatory lesions were present in the heart and brain, but gastrointestinal lesions characteristic of classic PDD were not observed. To investigate if this ABV2 isolate had reduced virulence, the virus was propagated in duck embryo fibroblasts and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
44
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 11 publications
2
44
0
1
Order By: Relevance
“…Although our findings strongly suggest that ABV is the cause of the clinical and pathological changes observed, formal proof of a causal relationship typically requires fulfilment of Koch's postulates. This was demonstrated for ABV/PDD in several species of parrots, but has yet to be carried out in waterfowl species Mirhosseini et al, 2011;Payne et al, 2011b;Piepenbring et al, 2012). ABV infection should, nonetheless, be included in the differential diagnosis for any Anseriform exhibiting upper gastrointestinal impaction or non-specific neurological signs and having non-suppurative inflammation of the central, peripheral or autonomic nervous systems.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although our findings strongly suggest that ABV is the cause of the clinical and pathological changes observed, formal proof of a causal relationship typically requires fulfilment of Koch's postulates. This was demonstrated for ABV/PDD in several species of parrots, but has yet to be carried out in waterfowl species Mirhosseini et al, 2011;Payne et al, 2011b;Piepenbring et al, 2012). ABV infection should, nonetheless, be included in the differential diagnosis for any Anseriform exhibiting upper gastrointestinal impaction or non-specific neurological signs and having non-suppurative inflammation of the central, peripheral or autonomic nervous systems.…”
Section: Discussionmentioning
confidence: 98%
“…ABV was first identified in 2008 and proposed as the aetiology of proventricular dilatation disease (PDD), a significant pathological syndrome that has been reported worldwide in more than 80 species of psittacine birds (Honkavuori et al, 2008;Kistler et al, 2008). Subsequent research, including inoculation studies in birds (Gancz et al, 2009;Gray et al, 2010;Mirhosseini et al, 2011;Payne et al, 2011b;Piepenbring et al, 2012) and investigations of outbreaks Gancz et al, 2010;Wunschmann et al, 2011;Heffels-Redmann et al, 2012), provided strong supporting evidence for a causal relationship. Psittacine birds affected with PDD exhibit various non-specific gastrointestinal and neurological signs with a high case fatality rate once clinical signs develop.…”
Section: Introductionmentioning
confidence: 95%
“…Among these psittacine viruses, PaBV-2 and PaBV-4 are most widely distributed1013 and both were experimentally confirmed to be causative agents of proventricular dilatation disease (PDD)141516171819.…”
mentioning
confidence: 99%
“…To date, 15 avian bornaviruses have been identified in a broad range of avian hosts, including Psittaciformes, Passeriformes and waterfowl (Afonso et al, 2016;Kuhn et al, 2015;Philadelpho et al, 2014). Parrot bornaviruses 2 (PaBV-2) and 4 (PaBV-4) are widely distributed in captive psittacine populations (Heffels-Redmann et al, 2011;Rubbenstroth et al, 2012) and were demonstrated to be the causative agents of proventricular dilatation disease (PDD) in these birds (Gray et al, 2010;Mirhosseini et al, 2011;Piepenbring et al, 2012;Rubbenstroth et al, 2014). Bornaviruses are slowly replicating viruses that can persistently infect neurons and various other cell types in susceptible hosts.…”
mentioning
confidence: 99%